Associations between postprandial triglyceride concentrations and sex, age, and body mass index: cross-sectional analyses from the Tromsø study 2015–2016 - Mikkelsen, Mari; Wilsgaard, Tom; Grimsgaard, Sameline; Hopstock, Laila A.; Hansson, Patrik (Frontiers in Nutrition, 2023)
Introduction Elevated serum triglyceride concentrations increase the risk of developing atherosclerosis, the leading cause of cardiovascular disease. Postprandial triglyceride concentrations have shown to be a stronger predictor of cardiovascular disease compared to fasting triglycerides. It is therefore clinically relevant to study patterns of postprandial triglyceride concentrations in a general adult population. Aims The aim of this cross-sectional analysis was to examine postprandial triglyceride concentrations in women and men, and the association with age, body mass index and menopausal status. Methods Non-fasting blood samples from 20,963 women and men aged 40 years and older, attending the seventh survey of the Tromsø Study (2015–2016), were analyzed for postprandial triglyceride concentrations using descriptive statistics and linear regression models. Self-reported time since last meal before blood sampling was categorized into 1-h intervals with 7+ hours considered fasting. Results Men had higher triglyceride concentrations compared to women. The pattern of postprandial triglyceride concentrations differed between the sexes. In women, the highest triglyceride concentration (19% higher compared to fasting level, p < 0.001) was found 3–4 h postprandially compared to 1–3 h in men (30% higher compared to fasting level, p < 0.001). In women, all subgroups of age and BMI had higher triglyceride concentrations than the reference group (age 40–49 years and BMI < 25 kg/m2), but no linear trend for age was observed. In men, triglyceride concentrations were inversely associated with age. Body mass index was positively associated with triglyceride concentration in both women (p < 0.001) and men (p < 0.001), although this association was somewhat modified by age in women. Postmenopausal women had significantly higher triglyceride concentrations compared to premenopausal women (p < 0.05). Conclusion Postprandial triglyceride concentrations differed in groups of sex, age, body mass index, and menopausal status.